Tantangan Pengajaran Ilmu Sharf di Era Digital : Analisis dan Solusi - Silma Salsa Bila (Reflection : Islamic Education Journal, 2025)
In the course of its long history, Islam in the archipelago has brought significant transformations in the way religious knowledge is delivered and learned. Literacy in pesantren has evolved from the traditional form of the yellow book to digital formats such as ebooks. In the 16th century, the yellow book emerged in the context of the archipelago as a very important cultural heritage of literacy in the tradition of Islamic scholarship. The yellow book is characterized by the yellowish color of the paper and is often referred to as al-kutub al-qadimah, which means classical or ancient books. Nahwu and Sharaf are two fundamental pillars of Arabic grammar that are essential for mastery of the language. Nahwu focuses on the structure of sentences as well as the function of words in the context of the sentence, while Sharaf studies changes in word forms and the process of derivation. These two disciplines complement each other in building a thorough understanding of the Arabic language. According to an article on Kompasiana, Nahwu and Sharaf materials are very integral in learning Arabic, similar to the role of grammar in English. This research adopts a qualitative approach with a library research method that aims to explore in depth various literatures related to Islamic character building in the digital era. Data collection is done by reviewing secondary sources, including books, scientific journals, academic articles, and documents.